Polysomnographic Predictors of Treatment Response to Cognitive Behavioral Therapy for Insomnia in Participants With Co-morbid Insomnia and Sleep Apnea: Secondary Analysis of a Randomized Controlled Trial - Sweetman, Alexander; Lechat, Bastien; Catcheside, Peter G.; Smith, Simon; Antic, Nick A.; O’Grady, Amanda; Dunn, Nicola; McEvoy, R. Doug; Lack, Leon (Frontiers in Psychology, 2021)
Objective: Co-morbid insomnia and sleep apnea (COMISA) is a common and debilitating condition that is more difficult to treat compared to insomnia or sleep apnea-alone. Emerging evidence suggests that cognitive behavioral therapy for insomnia (CBTi) is effective in patients with COMISA, however those with more severe sleep apnea and evidence of greater objective sleep disturbance may be less responsive to CBTi. Polysomnographic sleep study data has been used to predict treatment response to CBTi in patients with insomnia-alone, but not in patients with COMISA. We used RCT data to investigate polysomnographic predictors of insomnia improvement following CBTi, versus control in participants with COMISA. Methods: 145 participants with insomnia (ICSD-3) and sleep apnea (apnea-hypopnea index [AHI] ≥15) were randomized to CBTi (n=72) or no-treatment control (n=73). Mixed models were used to investigate the effect of pre-treatment AHI, sleep duration, and other traditional (AASM sleep macrostructure), and novel (quantitative electroencephalography) polysomnographic predictors of between-group changes in Insomnia Severity Index (ISI) scores from pre-treatment to post-treatment. Results: Compared to control, CBTi was associated with greater ISI improvement among participants with; higher AHI (interaction p=0.011), less wake after sleep onset (interaction p=0.045), and less stage 3 sleep (interaction p=0.005). No quantitative electroencephalographic, or other traditional polysomnographic variables predicted between-group ISI change (all p>0.09). Discussion: Among participants with COMISA, higher OSA severity predicted a greater treatment-response to CBTi, versus control. People with COMISA should be treated with CBTi, which is effective even in the presence of severe OSA and objective sleep disturbance.